2012
DOI: 10.1007/s11284-012-0999-4
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects in recruitment of trees, and relationship to seed dispersal patterns, in cleared strips in the Peruvian Amazon

Abstract: We investigated the spatial pattern of tree recruitment 15 years after clear‐cutting in two logged strips in the Peruvian Amazon, focusing on differences between seed dispersal modes and cohorts, and relating these to spatial patterns of seed dispersal in the years immediately following clearing. Most trees that recruited in logged strips belonged to taxa dispersed by birds or nonvolant mammals, with smaller numbers dispersed by bats or wind. Seed dispersal patterns differed, with few mammal‐dispersed seeds re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…Mostly using fecal analysis or seed traps, numerous studies in various human-modified landscapes across the Neotropics have documented the quantity and diversity of seeds carried by bats (mostly Carollia spp., Sturnira spp., Artibeus spp.) into a diverse range of disturbed habitats including pastures, agricultural areas, coffee plantations, and secondary forests (Medellín and Gaona 1999;Galindo-González et al 2000;García et al 2000;Aguiar and Marinho-Filho 2007;Hanson et al 2007;Wieland et al 2011;Castro-Luna and Galindo-González 2012b;García-Estrada et al 2012;García-Morales et al 2012;Gorchov et al 2013). Voigt et al (2012) showed that bats of the genus Carollia were likely to carry seeds from midsuccessional forest into adjacent primary forest, suggesting that directionality of seed transfer between disturbed areas and undisturbed forest may change with forest recovery.…”
Section: Effects On Selected Species Interactionsmentioning
confidence: 99%
“…Mostly using fecal analysis or seed traps, numerous studies in various human-modified landscapes across the Neotropics have documented the quantity and diversity of seeds carried by bats (mostly Carollia spp., Sturnira spp., Artibeus spp.) into a diverse range of disturbed habitats including pastures, agricultural areas, coffee plantations, and secondary forests (Medellín and Gaona 1999;Galindo-González et al 2000;García et al 2000;Aguiar and Marinho-Filho 2007;Hanson et al 2007;Wieland et al 2011;Castro-Luna and Galindo-González 2012b;García-Estrada et al 2012;García-Morales et al 2012;Gorchov et al 2013). Voigt et al (2012) showed that bats of the genus Carollia were likely to carry seeds from midsuccessional forest into adjacent primary forest, suggesting that directionality of seed transfer between disturbed areas and undisturbed forest may change with forest recovery.…”
Section: Effects On Selected Species Interactionsmentioning
confidence: 99%
“…Instead, changes in seed size are probably related to the lack of large forest bird species, transporting seeds into deforested areas (Gorchov et al. , ; Moran et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…) may lead to an uneven distribution of seed traits in deforested habitats (Gorchov et al. ). Consequently, seed dispersal limitation can affect the diversity of functional seed traits (Galetti et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus our study on bats as a biodiversity model system because they serve as good indicators of ecosystem health due to their species diversity, have varied life histories and morphologies, and are important in providing a variety of ecological services (Bennett, Radford, & Haslem, 2006;Castro-Luna, Sosa, & Castillo-Campos, 2007;Fenton & Rautenbach, 1998;Hein, Castleberry, & Miller, 2009). Bats play key roles in forest regeneration and ecosystem dynamics through the ecological services they provide combined with their high mobility and use of a variety of habitats (Gorchov et al, 2013;Kasso & Balakrishnan, 2013).…”
Section: Introductionmentioning
confidence: 99%